EVALUASI TATA KELOLA TEKNOLOGI INFORMASI BERDASARKAN DOMAIN EDM COBIT 2019 PADA BANK XYZ - Naufalarizqa Ramadha Meisa Putra (KHARISMA Tech, 2026)
Information technology (IT) governance plays an essential role in ensuring that the use of IT aligns with business objectives, delivers optimal value, and effectively manages risks, particularly in the banking sector. This study aims to evaluate the implementation of IT governance in the Evaluate, Direct, and Monitor (EDM) domain based on the COBIT 2019 framework at Bank XYZ. The research adopts a case study approach with an evaluative method through an assessment of the capability levels of processes EDM01 to EDM05. Data were collected through the review of IT policies and procedures, IT strategic planning documents, internal control reports, and discussions with relevant stakeholders during the observation period. The results indicate that all processes within the EDM domain have achieved capability level 4 (Managed). This finding suggests that IT governance at the top management level of Bank XYZ has been implemented in a structured, measurable, and quantitatively monitored manner. However, opportunities for further improvement remain, particularly in strengthening follow-up actions derived from IT benefits evaluation and ensuring consistent governance performance measurement across EDM processes. This study is expected to provide practical insights for enhancing strategic IT governance and to support future research on the application of the COBIT 2019 EDM domain in the banking industry.